2017
DOI: 10.1088/2058-6272/aa861d
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of electron density and electron temperature of a cascaded arc plasma using laser Thomson scattering compared to an optical emission spectroscopic approach

Abstract: As advanced linear plasma sources, cascaded arc plasma devices have been used to generate steady plasma with high electron density, high particle flux and low electron temperature. To measure electron density and electron temperature of the plasma device accurately, a laser Thomson scattering (LTS) system, which is generally recognized as the most precise plasma diagnostic method, has been established in our lab in Dalian University of Technology. The electron density has been measured successfully in the regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 32 publications
(44 reference statements)
0
12
0
Order By: Relevance
“…There is a software specially designed to automatically process the complex LTS spectra distorted by TGS and to determine T e and n e in real time. This LTS system has been employed successfully for cascaded arc plasma [46,47], nanosecond pulse discharge plasma [48], and RF plasma (Figure 8 shows the experimental setup) [49]. The employment of LTS system to precisely measure the temperature of helicon plasma is also possible, exciting, and expected in the ongoing work.…”
Section: Introductionmentioning
confidence: 99%
“…There is a software specially designed to automatically process the complex LTS spectra distorted by TGS and to determine T e and n e in real time. This LTS system has been employed successfully for cascaded arc plasma [46,47], nanosecond pulse discharge plasma [48], and RF plasma (Figure 8 shows the experimental setup) [49]. The employment of LTS system to precisely measure the temperature of helicon plasma is also possible, exciting, and expected in the ongoing work.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the capacity to produce high density plasma, cascaded arc plasma sources are selected to simulate the divertor plasma stream. Plasma-wall interactions (PWI) experiments with high particle flux have been performed in cascaded arc source type linear plasma devices such as Magnum-PSI [4], Pilot-PSI [5], CIMPLE-PSI [6], SCU-PSI [7], and DUT-PSI [8]. It has been demonstrated that the achievement of large ion flux requires both high magnetic field and huge gas fueling rate (typically several to tens of standard liters per minute (SLM)).…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al studied the electron temperature and electron density of the cascade arc plasma by combining TS and spectrometry. They found that the excited electron temperature obtained by spectrometry was about 40% higher than that obtained by TS, a serious discrepancy if used to characterize non-local thermodynamic equilibrium plasma [14]. In recent years, TS has been successfully used to diagnose LPP, and a series of reliable results have been obtained.…”
Section: Introductionmentioning
confidence: 99%